Pemberdayaan Masyarakat Adat Melalui Pengembangan Program Pelestarian Lingkungan Berbasis Ekonomi Lokal Di Desa Tabumela , Desa Ilotidea Kecamatan Tilango Kabupaten Gorontalo - Sumar, Warni Tune; Lamatenggo, Nina; Razak, Intan Abdul; Akadji, Fachrudin (CERED Indonesia Publishing, 2025)
Tubumela Village, Tilango District, is one of the villages located within the Gorontalo Regency Government. The village is located near the coast of Lake Limboto and the rice fields that serve as a dumping ground for waste from downstream. This waste poses a serious threat to the community living in the lake area because many people depend on the lake for their livelihoods. The training program on utilizing plastic waste to create economically valuable handicrafts is a science and technology application program that can provide solutions to the main problems faced by the community. The main problem is the still low level of processing plastic waste into an economically valuable product. This training aims for the community to understand and apply the process of utilizing plastic waste to create economically valuable decorative wall hangings and flower vases. The product is expected to be sold, thereby increasing community productivity and financial independence, and reducing the burden on landfills in accommodating plastic waste. With this training, it is hoped that it can increase the knowledge and skills of the people of Tabumela Village, Tilango District, in terms of managing and utilizing plastic waste, and enable them to create products from used plastic detergent packaging, bottled water, and plastic bags that have economic value. Other tendencies of the community, such as still throwing garbage in the wrong places, some even throwing garbage in ditches, burning garbage not in designated areas thus polluting the air, and improper waste management, meaning they are unfamiliar with waste types and waste separation rules, are also addressed. Therefore, the objectives of the thematic KKN service implementation in Phase II of 2025 are: (1) to conduct training and mentoring in environmental conservation, (2) to revive local wisdom culture by establishing a Gorontalo cultural studio, (3) to revive traditional cultures that are beginning to disappear, and (4) to conduct training and mentoring in natural resource management.